Quartz sand evaluation method for producing bubble-free quartz crucible and product thereof
Through the detection of the normal transparency, pH value, and high temperature heating of quartz sand, the transparency of the high temperature is to solve the problem of whether Jieying Sand can prepare air -free quartz crickets in the existing technology, and realize the high -quality and long life of quartz pupa.
Patent Information
- Application Number
- CN202411476737.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-24
AI Technical Summary
In the prior art, it is impossible to determine whether a quartz crucible without bubble layer can be prepared by detecting the purity and particle size of quartz sand.
By taking samples from a batch of quartz sand to be used, testing its normal temperature transparency and pH value, and then testing the transparency after heating at high temperature, if certain conditions are met, it is determined that the quartz sand can be used to prepare bubble-free quartz crucibles.
It ensures the bubble-free characteristics of the quartz crucible, improves the quality and service life of the crucible, and reduces resource waste and customer complaints.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of quartz sand, and in particular relates to a quartz sand evaluation method for producing bubble-free quartz crucibles and a product thereof. Background Art
[0002] With the advancement of the national carbon peak and carbon neutrality goals, and the accelerated deployment of the work of building a new power system with new energy as the main body, the status of the photovoltaic industry has been significantly improved, and it has ushered in a historic development opportunity; from the economic and technological perspectives, the importance of the semiconductor industry is very significant. Quartz crucible is the main auxiliary material used in upstream crystal pulling in the photovoltaic industry and the semiconductor industry. Its quality is closely related to the final conversion rate of the battery cell and the quality of the chip. The quality of the quartz crucible is affected by the quality of the raw material quartz sand. Some defects in the quartz sand can only be found through the production of quartz crucibles, such as small bubbles, bubble groups, large bubbles, etc. in the quartz crucible, resulting in poor appearance, affecting the pass rate and waste of resources; and the temperature of the quartz crucible during the pulling of single crystal silicon will reach 1480℃ to 1600℃, and the service life must be more than 400 hours. If there are many bubbles in the prepared quartz crucible, the microbubbles will expand and burst at high temperature, and quartz glass fragments will be brought into the silicon liquid and introduced into the single crystal silicon rod, causing crystal pulling failure, which will significantly affect the use effect of the quartz crucible.
[0003] At the same time, there are varying degrees of quality of quartz sand manufacturers on the market. If the quartz sand is not evaluated before use, the produced quartz crucibles may have bad bubbles, increased costs, waste of resources, and customer complaints due to material problems. However, the current evaluation of quartz sand only tests the purity and particle size of quartz sand, and it is impossible to determine whether a quartz crucible without a bubble layer can be prepared. Summary of the invention
[0004] In view of this, the present invention provides a quartz sand evaluation method and product for producing bubble-free quartz crucibles, so as to solve the technical problem in the prior art that it is impossible to judge whether a quartz crucible with a bubble-free layer can be prepared only by detecting the purity and particle size of the quartz sand.
[0005] To achieve the above objectives, this application adopts the following scheme:
[0006] A method for evaluating quartz sand for producing bubble-free quartz crucibles comprises the following steps:
[0007] S10. Take a number of samples from a batch of quartz sand to be used for spare use;
[0008] S20. Detect the transparency of the quartz sand sample at room temperature. If the proportion of quartz sand samples with a transparency less than 75% is less than or equal to 5%, proceed to step S30. If the proportion of quartz sand samples with a transparency less than 75% is greater than 5%, take a number of samples from a different batch of quartz sand and repeat step S20;
[0009] S30. Detect the pH of the quartz sand sample after step S20. If the pH is greater than or equal to 5 and less than or equal to 7, proceed to step S40. If the pH is less than 5, take a number of samples from another batch of quartz sand and repeat steps S20 to S30.
[0010] S40. Detect the transparency of the quartz sand sample after high-temperature heating in step S30. If the proportion of quartz sand with a transparency less than 75% is less than or equal to 5%, the evaluated quartz sand is obtained, and the quartz crucible prepared using the evaluated quartz sand is free of bubbles. If the proportion of quartz sand with a transparency less than 75% is greater than 5%, change a batch of quartz sand, take several samples therefrom, and perform steps S20 to S40.
[0011] Preferably, the step S20 specifically includes the following steps:
[0012] S21. The quartz sand sample is mixed with pure water and heated to a preset temperature, and allowed to stand for a preset time, wherein the solid-liquid ratio of the quartz sand to the pure water is 1:(1 to 2);
[0013] S22. After standing, detect the pH of the aqueous solution.
[0014] Preferably, the step S30 specifically includes the following steps:
[0015] S31. The quartz sand sample is heated at a temperature of 1450°C to 1620°C for 8h to 12h;
[0016] S32. After the heating is completed, the quartz sand sample is naturally cooled to room temperature, and the transparency ratio of the quartz sand sample is observed and counted under a microscope.
[0017] Preferably, the preset temperature is 24°C to 26°C.
[0018] Preferably, the preset duration is 8 minutes to 12 minutes.
[0019] A quartz crucible product made from the evaluated quartz sand in the quartz sand evaluation method for producing a bubble-free quartz crucible as described in any one of the above.
[0020] The technical solution adopted in this application can achieve the following beneficial effects:
[0021] The present invention provides a quartz sand evaluation method for producing bubble-free quartz crucibles. A plurality of samples are taken from a batch of quartz sand to be used, and the transparency of the quartz sand samples is detected at room temperature. If the proportion of quartz sand samples with a transparency less than 75% is greater than 5%, a large number of bubbles will appear in the produced quartz crucibles due to the high impurity content of the quartz sand samples, and it is determined that the quartz sand of this batch cannot be used. If the proportion of quartz sand samples with a transparency less than 75% is less than or equal to 5%, it means that the purity of the quartz sand samples is high and the impurity content is low, and it is preliminarily determined that the quartz sand samples can be used. Then, the pH value of the quartz sand samples is detected. If If the pH is less than 5, the sintering process of the produced quartz crucible will be affected, resulting in pores, cracks, etc. inside or on the surface of the crucible, thus affecting the service life and performance of the crucible. If the pH is greater than or equal to 5 and less than or equal to 7, the transparency of the quartz sand sample after high-temperature heating is tested, because the negative characteristics of the quartz sand will appear after high-temperature heating. If the transparency of the heated quartz sand sample is less than 75% and the proportion of quartz sand is less than or equal to 5%, it means that the quality of this batch of quartz sand is high, and evaluated quartz sand is obtained. The quartz crucible produced using the evaluated quartz sand has no bubbles, high quality and long service life. DETAILED DESCRIPTION
[0022] In order to facilitate the understanding of the present application, the present application is described in more detail. And the preferred embodiments of the present application are given. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present application more thoroughly understood.
[0023] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0024] A method for evaluating quartz sand for producing bubble-free quartz crucibles, characterized in that it comprises the following steps:
[0025] S10. Take a number of samples from a batch of quartz sand to be used for spare use;
[0026] S20. Detect the transparency of the quartz sand sample at room temperature. If the proportion of quartz sand samples with a transparency less than 75% is less than or equal to 5%, proceed to step S30. If the proportion of quartz sand samples with a transparency less than 75% is greater than 5%, take a number of samples from a different batch of quartz sand and repeat step S20;
[0027] S30. Detect the pH of the quartz sand sample after step S20. If the pH is greater than or equal to 5 and less than or equal to 7, proceed to step S40. If the pH is less than 5, take a number of samples from another batch of quartz sand and repeat steps S20 to S30.
[0028] S40. Detect the transparency of the quartz sand sample after high-temperature heating in step S30. If the proportion of quartz sand with a transparency less than 75% is less than or equal to 5%, the evaluated quartz sand is obtained, and the quartz crucible prepared using the evaluated quartz sand is free of bubbles. If the proportion of quartz sand with a transparency less than 75% is greater than 5%, change a batch of quartz sand, take several samples therefrom, and perform steps S20 to S40.
[0029] The quartz sand to be produced for quartz crucibles is used as the quartz sand to be evaluated, that is, a batch of quartz sand after arrival is evaluated. During the evaluation, a certain amount of quartz sand is first taken as a sample according to the normal quartz sand sampling method, which can represent the state of the whole batch of quartz sand. Under normal temperature and pressure, the quartz sand sample is placed under a microscope to observe its morphology. Generally speaking, the quartz particles observed are irregular three-dimensional, the size of the quartz particles is relatively uniform, and the particles are fully transparent or translucent. In this process, the transparency of the quartz particles observed is small. If the transparency is less than 75% and the proportion is greater than or equal to 75% (compared with the total amount observed this time), it can be explained that the quartz crucible prepared with this batch of quartz sand will have bubbles, affecting the quality of the crucible. Do not use this batch of quartz sand, change to another batch of quartz sand, take several samples from it, repeat this step, if the transparency is less than 75% and the proportion is less than 5%, it is necessary to proceed to the next step for further evaluation; too low pH value of quartz sand may affect the sintering process of the crucible, resulting in defects inside or on the surface of the crucible, such as pores and cracks, etc. The pH value that affects the service life and performance of the crucible is too low, which means that the quartz sand is more corrosive, which may cause corrosion damage to the production equipment, increase production costs and maintenance difficulties. Therefore, the pH of the quartz sand sample needs to be tested. If the pH of the quartz sand sample is less than 5, it can be said that the quartz crucible prepared using this batch of quartz sand will have bubbles, affecting the quality of the crucible, and the quartz sand of this batch will not be used. If the pH is greater than or equal to 5, it is necessary to proceed to the next step for further evaluation; then heat the quartz sand sample at high temperature, and then use a microscope to observe the morphology of the quartz particles after cooling. The transparency of the observed quartz particles is less than 75%, and the proportion is greater than or equal to 5%. It can be said that the quartz crucible prepared using this batch of quartz sand will have bubbles, affecting the quality of the crucible, and the quartz sand of this batch will not be used, and a new batch of quartz sand needs to be retested. If the transparency is less than 75% and the proportion is less than 5%, it means that the quality of this batch of quartz sand is high and can be used to produce quartz crucibles, and the produced quartz crucibles are free of bubbles, high in quality and long in service life.
[0030] Specifically, the step S20 specifically includes the following steps:
[0031] S21. The quartz sand and pure water are mixed and heated to a preset temperature, and allowed to stand for a preset time, wherein the solid-liquid ratio of the quartz sand to the pure water is 1: (1 to 2);
[0032] S22. After the standing is completed, the pH of the pure water is detected.
[0033] A quartz sand sample is mixed with pure water in a solid-liquid ratio of 1:(1 to 2), and then heated to a first preset temperature and allowed to stand for a first period of time. After the standing period, the pH of the solution is tested. If the pH of the quartz sand sample is less than 5, the batch of quartz sand will not be used to produce quartz crucibles.
[0034] Among them, the preset temperature is 24°C to 26°C, and the preset time is 8min to 12min.
[0035] Specifically, the step S30 specifically includes the following steps:
[0036] S31. The quartz sand sample is heated at a temperature of 1450°C to 1620°C for 8h to 12h;
[0037] S32. After the heating is completed, the quartz sand sample is naturally cooled to room temperature, and the transparency ratio of the quartz sand sample is observed and counted under a microscope.
[0038] When the quartz sand sample is observed under a microscope at room temperature and pressure, dominant defects of the quartz sand sample can be observed. However, the quartz sand sample may have negative defects, which cannot be manifested at room temperature and pressure. However, when the quartz sand is used to prepare a quartz crucible, the quartz crucible is easy to break during use (high-temperature heating) due to its unstable structure (with many bubbles). Therefore, this step needs to be added. Specifically, the quartz sand sample can be placed in a furnace and the temperature can be controlled at 1450°C to 1620°C, and heated for 8h to 12h. After heating, it can be naturally restored to a cooled state, and then placed under a microscope for observation and transparency. Specifically, photos can be taken and statistics can be made during observation.
[0039] A product of a quartz crucible made from the evaluated quartz sand in the quartz sand evaluation method for producing a bubble-free quartz crucible as described in any one of the above.
[0040] Quartz crucibles produced using evaluated quartz sand are bubble-free, high quality and long service life.
[0041] The following specific experimental examples are used to further illustrate the technical solutions and technical effects of the present invention. It should be noted that the following experimental examples are only for further explaining the present invention and do not limit the technical solutions of the present invention.
[0042] 1. Experimental Example 1
[0043] 1.1 Experimental methods
[0044] In this experiment, samples are taken from different batches of quartz sand (with different qualities) for testing. If a quartz sand sample satisfies steps S20 to S40 at the same time, the quartz sand is evaluated quartz sand and is marked as sample one; if a quartz sand sample only satisfies step S20, it is marked as sample two; if a quartz sand sample only satisfies step S30, it is marked as sample three; if a quartz sand sample only satisfies step S40, it is marked as sample four; if a quartz sand sample only satisfies steps S20 and S30, it is marked as sample five; if a quartz sand sample only satisfies steps S20 and S40, it is marked as sample six; if a quartz sand sample only satisfies steps S30 and S40, it is marked as sample seven; seven kinds of quartz crucibles are produced using samples one to seven respectively, and the bubble content and the state at high temperature of the seven kinds of quartz crucibles are tested respectively.
[0045] 1.2 Experimental procedures
[0046] Step 1: Purchase 20 batches of high-purity quartz sand in small quantities from the market, take 120 g of quartz sand at different depths from the 20 batches, and obtain 20 high-purity quartz sand samples;
[0047] Step 2: Place the twenty high-purity quartz sand samples under a 100-fold microscope for observation, and take photos to count the proportion of samples with a transparency less than 75%;
[0048] Step 3: Mix the 20 parts of high-purity quartz sand samples with 20 parts of pure water, each part of pure water is 120g, and heat to 26°C, then let it stand for 10 minutes, and use a pH detector to detect the pH of the obtained aqueous solution after the standing period;
[0049] Step 4: The twenty high-purity quartz sand samples were placed in a furnace and heated at 1500° C. for 10 hours. After heating, they were naturally cooled to room temperature and observed under a microscope at 100 times magnification. Photos were taken to count the percentage of samples with a transparency less than 75%. The results are shown in Table 1.
[0050] Table 1 Statistics of different batches of quartz sand
[0051]
[0052]
[0053] Note: The reason for the inconsistent data in Table 1 may be that the manufacturer sold inferior products as good ones or mixed lower-grade quartz sand.
[0054] It can be seen from the data in Table 1 above that sample 1 is quartz sand from batch 1, sample 2 is quartz sand from batch 9, sample 3 is quartz sand from batch 10, sample 4 is quartz sand from batch 3, sample 5 is quartz sand from batch 18, sample 6 is quartz sand from batch 15, and sample 7 is quartz sand from batch 7. Quartz crucibles are produced using samples 1 to 7 according to the normal production method of quartz crucibles to obtain seven kinds of quartz crucibles (marked as finished product 1, finished product 2, finished product 3, finished product 4, finished product 5, finished product 6, and finished product 7 for ease of description). Finished products 1 to 7 are tested, and the test results are shown in Table 2:
[0055] Table 2 Bubble quantity detection table of quartz crucibles prepared from different batches of quartz sand
[0056] Group describe determination Finished product 1 No bubbles in the transparent layer qualified Finished product 2 There are a lot of bubbles in the transparent layer Failure Finished product three There are a lot of bubbles in the transparent layer Failure Finished product 4 There are a lot of bubbles in the transparent layer Failure Finished product five There are a few bubbles in the transparent layer Failure Finished product six There are a few bubbles in the transparent layer Failure Finished product seven There are a few bubbles in the transparent layer Failure
[0057] The data in Table 2 above fully reflect that when evaluating whether there are bubbles in the quartz crucible produced using quartz sand, the steps in the method provided in the present application are indispensable, that is, when a batch of quartz sand needs to meet the conditions in steps 2 to 4 at the same time, the quartz crucible produced using the batch of quartz sand has no bubbles on the surface, high quality and long service life.
[0058] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or substitutions within the technical scope disclosed by the present invention, and these modifications or substitutions should be included in the protection scope of the present invention.
Claims
1. A method for evaluating quartz sand for producing bubble-free quartz crucibles, characterized in that: The following steps are involved: S10. Take a number of samples from a batch of quartz sand to be used for spare use; S20. Detecting the transparency of the quartz sand sample at room temperature. If the proportion of quartz sand samples with a transparency of less than 75% is less than or equal to 5%, proceed to step S30. If the proportion of quartz sand samples with a transparency of less than 75% is greater than 5%, a batch of quartz sand is replaced, and several samples are taken therefrom and step S20 is repeated; S30. Detecting the pH of the quartz sand sample after step S20, if the pH is greater than or equal to 5 and less than or equal to 7, proceeding to step S40, if the pH is less than 5, taking a number of samples from a different batch of quartz sand and repeating steps S20 to S30; S40. Detect the transparency of the quartz sand sample after high-temperature heating in step S30. If the proportion of quartz sand with a transparency less than 75% is less than or equal to 5%, the evaluated quartz sand is obtained, and the quartz crucible prepared using the evaluated quartz sand has no bubbles. If the proportion of quartz sand with a transparency less than 75% is greater than 5%, change a batch of quartz sand, take several samples therefrom and perform steps S20 to S40.
2. The method for evaluating quartz sand for producing bubble-free quartz crucibles according to claim 1, characterized in that: The step S20 specifically includes the following steps: S21. The quartz sand sample is mixed with pure water and heated to a preset temperature, and allowed to stand for a preset time, wherein the solid-liquid ratio of the quartz sand to the pure water is 1: (1 to 2); S22. After the standing is completed, the pH of the aqueous solution is detected.
3. The method for evaluating quartz sand for producing bubble-free quartz crucibles according to claim 1, characterized in that: The step S30 specifically includes the following steps: S31. The quartz sand sample is heated at a temperature of 1450°C to 1620°C for 8h to 12h; S32. After the heating is completed, the quartz sand sample is naturally cooled to room temperature, and the transparency ratio of the quartz sand sample is observed and counted under a microscope.
4. The method for evaluating quartz sand for producing bubble-free quartz crucibles according to claim 2, characterized in that: The preset temperature is 24°C to 26°C.
5. The method for evaluating quartz sand for producing bubble-free quartz crucibles according to claim 2, characterized in that: The preset duration is 8 min to 12 min.
6. A quartz crucible product made of the evaluated quartz sand in the method for evaluating quartz sand for producing a bubble-free quartz crucible according to any one of claims 1 to 5.
Citation Information
Cited By
Detection method for evaluating high-temperature structural stability of quartz crucible
CN121521201A
Test methods for evaluating the high-temperature structural stability of quartz crucibles
CN121521201B